THE A.NTHELMINTIC ACTIVITY OF HUNTERIA UMBELLATA K SCHUM (FAM. ApOCYNACEAE) EXTRACTS (Biological Sciences - PJSIR, 2001)
Aqueous and methanolic extracts of the leaves, seeds and stem bark of Hunteria umbel/ala. K. Schum, were tested foranthelmintic activity. The extracts of the leaves, seeds and stem bark have significant anthelmintic activity when comparedwith normal saline which acted as control. The methanolic extract of the stembark had the highest activity for all theextracts. However, the activity of the aqueous extract of the seeds was more effective than the aqueous extract of the leavesand stembark.